The health system and access to treatment in patients with cervical cancer in Mexico - Arango-Bravo, Eder A.; Cetina-Pérez, Lucely del Carmen; Galicia-Carmona, Tatiana; Castro-Eguiluz, Denisse; Gallardo-Rincón, Dolores; Cruz-Bautista, Ivette; Duenas-Gonzalez, Alfonso (Frontiers in Oncology, 2022)
Cervical cancer is tightly related to a low Human Development Index. Among the approximately 604,000 new cases and 342,000 deaths worldwide by 2020, the rates in developed and developing countries vary from 18.8 vs. 11.3 per 100,000 and 12.4 vs. 5.2 per 100,000 for incidence and mortality, respectively. These figures result from contrasting effects on secondary prevention programs and treatment access. In Mexico, CC is the second in incidence and mortality among women; nevertheless, the age-standardized CC mortality rate has decreased from 12 per 100,000 women in 1979 to 5.7 per 100,000 women in 2020 due in part to increased screening coverage. Still, around two-thirds of patients present with locally advanced disease at diagnosis. Data from our country demonstrate that even socially disadvantaged CC patients achieve "standard" survival outcomes if treatment is granted. Mexico is an upper-middle income country (UMIC) with a public health system aiming to provide 100% health coverage. Currently, employment-based social insurance covers approximately 60% of the population, while the public health infrastructure to cover the remaining 40% is planned to increase. However, the annual government spending on health is not increased accordingly. It remains at 3% of Gross Domestic Product (GDP) which is well below the 6% recommended by the Organization for Economical Cooperation and Development. Because of that, further advances in CC control in Mexico are not envisioned to occur soon. The perspectives for global CC control are not encouraging. From the primary and secondary prevention, 8 years after launching the first Human Papilloma Virus (HPV)-vaccine, the global coverage of the final HPV dose for 2019 is estimated at 15%, which is far from the proposed 90% by 2030. Moreover, only 36% of women aged 30 - 40 have been screened in their lifetime, far from the 70% target. The perspectives for adequate treatment of invasive diseases with a target of 90% appears unachievable because the known existing shortage of oncological infrastructure worldwide. In conclusion, despite numerous analyses from the epidemiological and oncological perspectives, the fact is that worldwide, CC represents a heavy health burden derived from the social and economic global inequalities.